KAJIAN PERBANDINGAN PERTUMBUHAN IKAN BARONANG (SIGANUS CANALICULATUS) DALAM KERAMBA JARING DASAR PADA KONDISI PADANG LAMUN YANG BERBEDA DI PULAU LANTANG PEO KABUPATEN TAKALAR - Muh Aryan . R Suci; Andi Tamsil; Harlina Harlina (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
Muh. Aryan R Suci. Growth of Baronang Fish (Siganus canaliculatus) in Basic Net Cages in Different Seagrass Conditions on Lantang Peo Island, Takalar Regency. Lantang Peo Island which is one of the islands which is covered by several types of seagrass. Data collection was carried out from September to October 2016 at the Lantang Peo estuary. The first treatment is observation of density, cover and identification of seagrass. The second treatment is measuring water quality and the last one is measuring the weight and length of the baronang fish. Observation of seagrass species obtained Enhalus accoroides and Thalassia hempichii species. The total density of seagrass at Station I was 47 (teg / m2) 10.03% cover of seagrass, 70 (teg / m2) density of seagrass at Station II was 17.12% and the total density of seagrass at Station III was 90 (teg / m2) 18.13%. Observation of the absolute growth of baronang fish weight at station I of 1 gr. At station II the absolute weight growth of fish is 3 gr and at station III the absolute weight growth of fish is 5 gr. Observations of the absolute length increase of fish at Station I were 1 cm, the absolute length increase of fish at Station II was 2 cm and the absolute length increase of fish at Station III was 3 cm. This difference occurs due to the different density structure of the seagrass at each station.